2010
DOI: 10.1007/s10792-010-9362-3
|View full text |Cite
|
Sign up to set email alerts
|

Electronic compliance monitoring of topical treatment after ophthalmic surgery

Abstract: The success of many medical treatments is built on compliance. Electronic monitoring is the most accurate tool to quantify compliance by measuring adherence. In order to assess the efficiency of a recently introduced miniature monitoring device for eye drop application, we evaluated adherence in ophthalmic patients undergoing post-operative shortterm topical treatment. This pilot study enrolled 30 outpatients (mean age 61.8 ± 18.5 years) after cataract (n = 24) and glaucoma filtration surgery (n = 6) applying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…Historically, compliance with dosing of topical ocular medications in eye drop form has been poor [14,15,36]. Patients, particularly the elderly, can find the complicated dosing regimens required with some topical ophthalmic medications to be challenging [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, compliance with dosing of topical ocular medications in eye drop form has been poor [14,15,36]. Patients, particularly the elderly, can find the complicated dosing regimens required with some topical ophthalmic medications to be challenging [14].…”
Section: Discussionmentioning
confidence: 99%
“…Patients, particularly the elderly, can find the complicated dosing regimens required with some topical ophthalmic medications to be challenging [14]. An electronic monitoring study in cataract surgery patients who were asked to dose steroid and antibiotic drops fives time daily for 2 weeks, found only about half were compliant with their medication dosing [36]. This noncompliance, combined with inaccurate drop administration problems discussed above, can put patients at risk for post-surgical complications.…”
Section: Discussionmentioning
confidence: 99%
“…Prescription eye drops can be expensive, and treatment regimens are often complex, sometimes including up to three medications, each requiring different numbers of drops at various intervals throughout the day for up to several weeks [1,8]. A compliance monitoring study found that cataract surgery patients only applied half of the prescribed number of postoperative drops [9]. A separate video-based analysis found that 93% of eye-drop naïve patients used improper technique when applying postoperative drops [10].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional bottles of eye drops can be equipped with the recently developed Travatan Dosing Aid (Alcon Laboratories, Inc., Fort Worth, TX), a miniature monitoring device that records the time and day when the lever that administers the medication is depressed. (Hermann et al, 2010;Friedman et al, 2009;Okeke et al, 2009a) Different patterns of adherence behavior can be identified from the downloaded data, and it was accurate in 93% in patients. While the majority of patients found it made dispensing drops easier, it also contains a reminder that can help increase adherence.…”
Section: Methods For Improving Adherencementioning
confidence: 99%